Significant Relationship between Overweight and Hypertension in the Elderly - Suwanda Wahyudin; Rudolf Andean; Lilik Sukesi (Althea Medical Journal, 2020)
Background: Hypertension is one of the degenerative diseases that commonly occurs in the elderly, however, the etiology is still unclear. One of the risk factors is overweight. This study aimed to investigate the relationship between overweight and hypertension in the elderly living in Hegarmanah village.Methods: A cross-sectional analytic study was conducted from September to November 2013, including 100 elderly in Hegarmanah village Jatinangor, Sumedang, using a cluster sample technique. The data of body weight, height, and blood pressure were obtained after informed consent.Results: In total, 58 females and 42 males were included. The nutritional status was underweight (9%), normal (45%), overweight (31%), and obese (15%).  Hypertension among the elderly was normal (4%), prehypertension stage 1 (18%), hypertension stage II (24%), and hypertension stage III (54%). The hypertension was occurred in 43.6% non-overweight group and 56.4% in the overweight group, resulting in a significant relationship between overweight and hypertension in the elderly (p=0.001).Conclusions: The high prevalence of hypertension among the elderly who were overweight suggests a better promotion in lifestyle control, a particularly nutritional program for the elderly to manage hypertension and its complication.